اعداد الموازنات التخطيطية باستخدام الحاسوب - أ.د. قاسم محسن الحبيطي; وحيد محمود رمو (PROSPECTIVE RESEARCHES, 2023)
Planning balances are considered one of the most important methods which are used in management. It is important because it reflects the condition of the activity in the future. Taking into consideration the fact that accountancy attempts to follow the development in technology, managerial accounting (a branch of accountancy) aims at following this development through the use and application of computers in all the fields and methods of accountancy, including planning balances.